Reevaluating anticoagulation therapy for sepsis-associated disseminated intravascular coagulation based on endothelial glycocalyx shedding quantification: a single-center, retrospective, observational pilot study - Keiko Suzuki; Keiko Suzuki; Akio Suzuki; Kazuyuki Sumi; Kodai Suzuki; Kodai Suzuki; Tomoaki Yoshimura; Shozo Yoshida; Nobuyuki Tetsuka; Hideshi Okada; Hideshi Okada (Frontiers in Medicine, 2025)
BackgroundSepsis-induced disseminated intravascular coagulation (DIC) is associated with critical conditions and linked to a high mortality rate. Anticoagulants such as recombinant human soluble thrombomodulin (rhTM) and antithrombin are used to treat sepsis-associated DIC; however, their efficacy remains controversial. Syndecan-1, a biomarker of endothelial glycocalyx injury, has been proposed as a potential indicator of sepsis severity and prognosis. This study aimed to investigate the association between serum syndecan-1 levels and recovery from sepsis-associated DIC in patients treated with anticoagulants.MethodsA retrospective observational study was conducted at Gifu University Hospital. Patients aged ≥ 20 years with sepsis-associated DIC treated with anticoagulants (rhTM and antithrombin III) for ≥2 days were included. Serum syndecan-1 levels were measured at baseline, during treatment, and at 2 days after therapy. The relationship between syndecan-1 levels and recovery from DIC, assessed using the Japanese Association for Acute Medicine (JAAM)-2 and JAAM-DIC criteria, was analyzed.ResultsThirteen patients were included. Serum syndecan-1 levels peaked at the start of anticoagulation therapy, decreased during treatment, and increased after cessation of therapy. Recovery from DIC was associated with lower post-treatment syndecan-1 levels (p < 0.05). In patients who did not recover, syndecan-1 levels increased by more than 30%, correlating with poor outcomes, including mortality.ConclusionSyndecan-1 is a potential marker for monitoring endothelial injury and recovery from sepsis-associated DIC. Extended anticoagulant therapy may improve outcomes by reducing endothelial damage and potentially enhancing recovery from DIC in patients with sepsis. Further large-scale studies are required to confirm these findings.